2013
DOI: 10.1371/journal.pone.0073927
|View full text |Cite
|
Sign up to set email alerts
|

Enterohemorrhagic Escherichia coli as Causes of Hemolytic Uremic Syndrome in the Czech Republic

Abstract: BackgroundEnterohemorrhagic Escherichia coli (EHEC) cause diarrhea-associated hemolytic uremic syndrome (D+ HUS) worldwide, but no systematic study of EHEC as the causative agents of HUS was performed in the Czech Republic. We analyzed stools of all patients with D+ HUS in the Czech Republic between 1998 and 2012 for evidence of EHEC infection. We determined virulence profiles, phenotypes, antimicrobial susceptibilities and phylogeny of the EHEC isolates.Methodology/Principal FindingsVirulence loci were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 80 publications
0
25
0
1
Order By: Relevance
“…The O157 serotypes of STEC are occasionally sorbitol-negative (24,25). However, sorbitolfermenting O157 strains have begun to be reported (26)(27)(28)(29). In our study, we reported that the E.coli O174:H21 strain (n = 1) that fermented sorbitol was isolated from the pediatrics service, but other STEC strains (n = 4) were not sorbitol-fermenting.…”
Section: Discussionmentioning
confidence: 65%
“…The O157 serotypes of STEC are occasionally sorbitol-negative (24,25). However, sorbitolfermenting O157 strains have begun to be reported (26)(27)(28)(29). In our study, we reported that the E.coli O174:H21 strain (n = 1) that fermented sorbitol was isolated from the pediatrics service, but other STEC strains (n = 4) were not sorbitol-fermenting.…”
Section: Discussionmentioning
confidence: 65%
“…STEC O26:H11/H-of ST29 represent a highly virulent clone found first in Germany in the 1990s as a cause of HUS (Zhang et al 2000;Bielaszewska et al 2013). It spread through Europe to Germany, Belgium, Czech Republic, Italy, Slovakia, Scotland and Switzerland where it frequently cause a HUS in human patients, even with fatal cases (Chase-Topping et al 2012;Bielaszewska et al 2013;Marejkov a et al 2013;Zweifel et al 2013). Latest studies performed in Switzerland shows that healthy cattle could constitute a potential reservoir and source of new STEC O26 pathotypes (Zweifel et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, STEC O26 are one of serogroups of STEC responsible for most of the HUS cases occurring in the European countries (EFSA, 2013). In mid-1990s in Germany emerged a highly virulent clone of STEC O26:H11/H-Sequence Type 29 (ST 29) and spread over eight European countries (Zhang et al 2000;Chase-Topping et al 2012;Bielaszewska et al 2013;Marejkov a et al 2013;Zweifel et al 2013). This clone harbours stx2a as the only Shiga toxin gene and comprises characteristic plasmid genes profile (ehxA+, etpD+, katPÀ, espPÀ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are as well EHEC serotypes that are non-sorbitol fermenters (NSF) giving the characteristic growth on SMAC but are not H7 strain 30 well as non-O157 serotypes 31 . While E. coli O157 are popularly known to be non-sorbitol fermenting organisms 31 there are reports of Sorbitol fermenting (SF) E. coli O157 with HUS ability from Czech 32 and from Scotland 33 .…”
Section: Discussionmentioning
confidence: 99%